2021
DOI: 10.1029/2020je006572
|View full text |Cite
|
Sign up to set email alerts
|

Geologic History and Crater Morphology of Asteroid (162173) Ryugu

Abstract: Crater morphology and surface age of asteroid (162173) Ryugu are characterized using the high‐resolution images obtained by the Hayabusa2 spacecraft. Our observations reveal that the abundant boulders on and under the surface of the rubble‐pile asteroid affect crater morphology. Most of the craters on Ryugu exhibit well‐defined circular depressions, unlike those observed on asteroid Itokawa. The craters are typically outlined by boulders remaining on the rim. Large craters (diameter > 100 m) host abundant and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…PolyCam images of the crater interior also show evidence of possibly ongoing small-scale creep where the crater wall is now the steepest (Figures 6(a) and (b)), near the current maximum slope of 40°± 10°. In contrast to our observations of Bennu, wall slumping on Ryugu has been observed only in its largest crater, Urashima (Sugita et al 2019;Cho et al 2021).…”
Section: Local Context Of the Nightingale Sitecontrasting
confidence: 99%
“…PolyCam images of the crater interior also show evidence of possibly ongoing small-scale creep where the crater wall is now the steepest (Figures 6(a) and (b)), near the current maximum slope of 40°± 10°. In contrast to our observations of Bennu, wall slumping on Ryugu has been observed only in its largest crater, Urashima (Sugita et al 2019;Cho et al 2021).…”
Section: Local Context Of the Nightingale Sitecontrasting
confidence: 99%
“…These findings are consistent with most recent analysis, e.g., refs. 23 – 25 , but in contrast to previous studies which proposed much older surface ages (~1 Gyr) based on low cratering efficiencies, corresponding to strength regime scaling, e.g., refs. 22 , 26 .…”
Section: Discussionmentioning
confidence: 59%
“…Hirata et al (2020) provided a comprehensive list of impact craters larger than 20 m on Ryugu and discussed their spatial distribution. More detailed morphological studies of the craters are reported in Noguchi et al (2021) and Cho et al (2021). A statistical randomness analysis by Hirata et al (2020) confirmed that those craters are concentrated in the equatorial region (30°S-30°N) rather than follow a random distribution.…”
Section: Asteroid Ryugu Revealed By Hayabusa2mentioning
confidence: 82%
“…Hence, our estimated time scale of the rotational deceleration is comparable to the time that Ryugu has spent in the near-Earth orbit. Recently, Cho et al (2021) estimated the surface age of each geological unit on the asteroid.…”
Section: Implications For Geologic History Of Ryugumentioning
confidence: 99%
See 1 more Smart Citation